Fonder From Afar: Distance, Leadership, and the Legitimacy of the EU - Femke van Esch; Sebastiaan Steenman (Politics and Governance)
Why do people support political leadership? This age-old question is increasingly relevant in international politics and especially for the EU, which is seen as suffering from a legitimacy deficit. In EU studies, the question of legitimacy has been approached predominantly from an institutional perspective. However, in times of increased mediatisation and personalisation of politics, leaders play an increasingly important role in determining the legitimacy of politics in the eyes of the people, especially in “distant” polities like the EU. Following these insights from leadership studies, this article examines to what extent citizens’ trust in the EU is influenced by their assessment of different types of EU leaders, as well as distance. A unique survey of citizens’ assessments of EU leaders on five dimensions—being democratically elected, credibility, ideology, social identification, and emotions—is used to answer this question. The study unexpectedly finds that the more distant the leader, the more positive people’s evaluation of their EU leadership. Moreover, the assessment of these leaders significantly and strongly correlates with the extent to which citizens trust the EU. This finding holds for all three categories of EU leaders but is strongest for the most distant leaders. No support, however, is found for the expectation that, in the case of increased distance between leaders and followers, the psychological aspects of legitimacy dominate over the more utilitarian considerations underlying people’s trust in the EU.